CNSC-36. VRK1 IS A PARALOG SYNTHETIC LETHAL TARGET IN VRK2-METHYLATED GLIOBLASTOMA. (14th November 2022) - Shields, Julie; Meier, Samuel; Bandi, Madhavi; Ferdinez, Maria Dam; Engel, Justin; Mulkearns-Hubert, Erin; Hajdari, Nicole; Shen, Binzhang; Hubert, Christopher; Mitchell, Kelly; Zhang, Wenhai; Zhao, Shan-chuan; et al.
Abstract: Synthetic lethality — a genetic interaction that results in cell death when two genetic deficiencies co-occur but not when either deficiency occurs alone — can be co-opted for cancer therapeutics. A pair of paralog genes is among the most straightforward synthetic lethal interaction by virtue of their redundant functions. Here we demonstrate a paralog-based synthetic lethality by targeting Vaccinia-Related Kinase 1 (VRK1) in Vaccinia-Related Kinase 2 (VRK2)-methylated glioblastoma (GBM). VRK2 is silenced by promoter methylation in approximately two-thirds of GBM, an aggressive cancer with few available targeted therapies. Genetic knockdown of VRK1 in VRK2-methylated GBM cell lines and patient-derived models was lethal and resulted in decreased activity of the downstream substrate Barrier to Autointegration Factor (BAF), a regulator of post-mitotic nuclear envelope formation. VRK1 knockdown, and thus reduced BAF activity, caused nuclear lobulation, blebbing and micronucleation, which subsequently resulted in G2/M arrest and DNA damage. The VRK1-VRK2 synthetic lethal interaction was dependent on VRK1 kinase activity and was rescued by ectopic VRK2 expression. Knockdown of VRK1 led to robust tumor growth inhibition in VRK2-methylated GBM xenografts. These results indicate that inhibiting VRK1 kinase activity could be a viable therapeutic strategy in VRK2-methylated GBM.